Antecedents of Job Satisfaction Mediated by Work Motivation - Nurmasari, Eldisa Zenita; Endratno, Hermin; Suyoto; Haryanto, Totok (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the antecedents of job satisfaction mediated by work motivation. This research is quantitative using Partial Least Square version 4.0. The sample uses census techniques of 102 respondents. The results of the research individual characteristics and workload have a positive and significant effect on job satisfaction, job characteristics, and organizational culture do not affect job satisfaction, organizational culture has no significant effect on job satisfaction, job characteristics have a positive and significant effect on work motivation, organizational culture positive and significant effect on work motivation, workload has a significant effect on work motivation, work motivation does not affect job satisfaction, individual characteristics, job characteristics, organizational culture, and workload cannot mediate employee work motivation on job satisfaction.